At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
NEED HELP PLEASE!!!!!!!!!!!!!!!!!!!!!!
3x - y = -3 (original) -3x + y = 3 (multiply the whole thing by -1 y = 3x + 3 (add or subtract to get y alone) your slope is 3, so m=3 you can substitute your point into (y - y1) = m (x - x1) to generate an equation for it. y + 2 = 3 ( x - 4 ) y + 2 = 3x - 12 y = 3x - 14
@Zilther THANKS! THERE ARE MORE PROBLEMS LIKE THIS DO U MIND IF I TRY THEM ON MY OWN AND YOU COULD HELP ME CORRECT THEM AND TELL ME WHERE I WENT WRONG?
if you say @zilther it will alert me and I can help you through more of them if you like. :)
@@zilther THE QUESTIOIN IS : Write the equation of the line that is parallel to the line y = −3x + 12 and passes through the point (−1, 6)
I found the slop m=-9 but im now stuck
okay, look at the formula that's up there ^ ( y - y1 ) = m ( x - x1 ) substitute your x and y vales for y1 and x1, then simplify and tell me what you get.
your x1 and y1 values are the ones that you said the line passes through, ( -1 , 6 )
parallel lines only share the same slope, the y-intercept doesn't matter at all, so keep that in mind.
(y2-6) = -9 (x2-(-1) @zilther
there's no y2, lol you end up with y - 6 = -9 ( x - (-1)) or y - 6 = -9 ( x + 1 ) if you simplify it. just follow PEMDAS and balance the equation. :)
y = -6 = 9? @Zilther
sorry for the late response. y - 6 = -9 ( x - (-1) ) y - 6 = -9 ( x + 1 ) <- simplified a little to get rid of the parenthesis you follow the distributive property -9 * x = -9x -9 * 1 = -9 so you end up with y - 6 = -9x - 9 after getting rid of the parenthesis y - 6 = -9x - 9 add 6 to each side to get rid of the -6 on the side of y y = -9x - 3 there's your equation.
thats none of the answers tho Ay = one thirdx + 7 B. y = −3x + 3 C.y = one thirdx + 3 D. y = −3x + 7 @Zilther
I have no idea what happened in that math. your slope is -3, and the point is ( -1 , 6 ) ( y - 6 ) = -3 ( x - (-1) ) y - 6 = -3 ( x + 1 ) y - 6 = -3x - 3 y = -3x + 3 <- that's the right answer
sorry about that O.o;